Muscle Mass Difference among Patients With Chronic Kidney Disease Stage 3 to Stage 5 - Ivena Ivena; Rudi Supriyadi; Setiawan Setiawan (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Low muscle mass is one of the complications of chronic kidney disease (CKD), that may occur due to the accumulation of uremic toxins and other mechanisms related to CKD. The aim of this study was to explore the difference of muscle mass among CKD patients stage 3 to stage 5.Methods: A cross-sectional study was conducted with comparative analysis, using secondary data collected during the year 2017 by total sampling method. Subjects were patients aged over 18 years with CKD stage 3 to stage 5 from three hospitals in Bandung. Chronic Kidney Disease stages were determined based on Glomerular Filtration Rate. Muscle mass data was determined using Bioelectrical Impedance Analysis, collected from previous research. Data were analyzed usingone-way ANOVA or Kruskal-Wallis test.Results: One hundred subjects consisting of 57 men and 43 women were included in in this study with the mean muscle mass was 26.29%±4.86, of whom 67% of the patients had low muscle mass. There was no difference between male (27.21%±3.82) and female (28.36%±4.67). The muscle mass among patients withCKD stage 3 to stage 5 showed no significant results (p>0.05).Conclusions: There is no difference in muscle mass among CKD stage 3 to stage 5.